Effects of extraction, purification and drying on the physicochemical properties of durian seed gum - Bahareh, Tabatabaee Amid (2011)
The long-term goal of the current study was to look into the possibility of applying the biorefinery process for utilizing the main biomass of durian fruit. The main objective was to investigate the effect of extraction, purification and drying on the chemical composition, physicochemical and functional properties of durian seed gum. The efficiency of two aqueous and chemical extraction techniques was compared under the optimum extraction conditions to determine the most suitable extraction condition resulted in the crude durian seed gum with desirable functional properties. For further improvement of functional properties of crude gum, the determination of most suitable purification and drying techniques resulting in the purified durian seed gum with desirable properties was carried out. The results indicated that durian seed gum exhibited a typical ‘pseudoplastic or shear-thinning rheological behavior’. In fact, the viscosity of durian seed gum decreased when the shear rate was increased. The durian seed gum showed more viscous (liquid like) behavior rather than the elastic (solid like) behavior. This is typical rheological behaviour of diluted gum solution, when the molecules cannot entangle and produce a network structure during oscillatory stress. This could be due to the random-coil polysaccharide structure which behaved like a liquid when exposed to low frequencies of oscillation. The carbohydrate analysis showed that the major monosaccharide composition of crude durian seed gum include D-galactose (57.2 ± 3.2), glucose (41.8 ± 3.9), and small contents of arabinose (0.6 ± 0.03) and xylose (0.4 ± 0.06). The current study revealed that the durian seed gum may be classified as a galactan or arabinogalactans rather than a galactomannan. The results indicated that the chemical extraction variables exhibited the highest significant (p < 0.05) effect on the oil-holding capacity (OHC) and extraction yield, respectively. Among all chemical extraction variables, the soaking temperature and decolouring time showed the most significant (p < 0.05) effect on the physicochemical and functional properties of the crude durian seed gum. The optimum chemical extraction (i.e. the decolouring time ~119 min, soaking time ~1.5 h and soaking temperature 16.5 °C) resulted in the most desirable physicochemical properties. The results indicated that the purification process significantly (p < 0.05) improved the solubility of crude durian seed gum. This could be explained by the fact that the purification process resulted in the significant (p < 0.05) decrease in the protein content and some impurities in the chemical structure of crude durian seed gum. The current study revealed that the purification method C (using saturated barium hydroxide) resulted in the highest protein content, maximum solubility and OHC as well as the most desirable viscous modulus (Gʺ) among all purification methods. In addition, the purified seed gum using saturated barium hydroxide also provided high WHC, large specific surface area and relatively high purification yield and viscosity. Therefore, the present study suggests that the purification process using saturated barium hydroxide is recommended as the most suitable purification technique for durian seed gum. Finally, the effect of four different drying methods (namely oven drying (105 °C), vacuum oven drying, freeze drying and spray drying) on the chemical composition and physicochemical properties of purified durian seed gum was investigated. In this study, the drying process led to improve the solubility of purified durian seed gum. This observation could be explained by the significant (p < 0.05) effect of drying process on the carbohydrate composition and protein content of purified durian seed gum. In fact, the drying process resulted in (i) decrease the protein, xylose and arabinose contents and (ii) increase the glucose and galactose contents. The present study revealed that the freeze drying resulted in the durian seed gum with smallest average droplet size. In addition, the freezedried seed gum also provided the highest protein content and maximum solubility, specific surface area, viscosity and OHC among other samples. Therefore, the present study recommends the freeze drying as the most suitable drying technique for the durian seed gum.